Analisis Koefisien Penyesuaian Harga Dan Efektifitas Penyerapan Informasi Baru di Bursa Efek Jakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
On the stock market, new information is "the basic need" for investors or traders, since they use it this information in their investment decision making. The question then arises as to how fast this new information is reflected in stock price changes. Most financial economist agree that an efficient market adjust the stock price rapidly as a result of new informa-tion. The main purpose of this research is how to measure the speed of market adjustment, and the effectiveness of the absorption of new informa-tion, using the Aswath Damodaran model. The price adjustment 10-efficient (g) is used to measure the speed of market adjustment, since it is an indicator of and gives the information about, return processes in the past. We find evidence that JSX tends to "overreact" or "overshoot" in its absorption of new information, resulting in stock prices on the JSX deviating significantly from their intrinsic value, with these deviations occurring in almost all absorption processes. The evidence is consistent with the overreaction hypothesis. The JSX needs 22 days to completely absorb new information. Other results show that there is no information noise on the JSX, reflecting the government's success in making the JSX a "better market" for investors and traders.